Projection-based dynamic tomography. (3rd November 2021) - Jailin, Clément; Roux, Stéphane; Sarrut, David; Rit, Simon
Abstract: Objective . This paper proposes a 4D dynamic tomography framework that allows a moving sample to be imaged in a tomograph as well as the associated space-time kinematics to be measured with nothing more than a single conventional x-ray scan. Approach . The method exploits the consistency of the projection/reconstruction operations through a multi-scale procedure. The procedure is composed of two main parts solved alternatively: a motion-compensated reconstruction algorithm and a projection-based measurement procedure that estimates the displacement field directly on each projection. Main results . The method is applied to two studies: a numerical simulation of breathing from chest computed tomography (4D-CT) and a clinical cone-beam CT of a breathing patient acquired for image guidance of radiotherapy. The reconstructed volume, initially blurred by the motion, is cleaned from motion artifacts. Significance . Applying the proposed approach results in an improved reconstruction quality showing sharper edges and finer details.